Transformational Applications of Human Cardiac Organoids in Cardiovascular Diseases - Xuan, Wanling; Tipparaju, Srinivas M.; Ashraf, Muhammad (Frontiers in Cell and Developmental Biology, 2022)
Organoid technology has significantly advanced in recent years and revolutionized the field for generation of organs using in vitro systems (a.k.a “organs in a dish”). The use of pluripotent stem cells or tissue derived cells for generating a 3-dimensional culture system to recapitulate the architecture and function of the organ is central in achieving and improving organoid systems. Unlike most organs in the body, very little progress has been made in cardiac organoid due to its structural complexity and vascularization. In this review, we will discuss the current applications of human cardiac organoids for cardiac disease modeling, drug discovery, drug cardiotoxicity testing, and clinical applications.